Critical investments in bioregenerative life support systems for bioastronautics and sustainable lunar exploration - D. Marshall Porterfield; Dana Tulodziecki; Raymond Wheeler; Mai’a K. Davis Cross; Oscar Monje; Lynn J. Rothschild; Richard J. Barker; Hansjorg Schwertz; Steven Collicott; Som Dutta (npj Microgravity)
Abstract NASA and the CNSA have both released plans for lunar human exploration. This paper reviews those plans through the lens of strategic capability development. It examines the history of NASA’s development of bioregenerative space habitation systems and shows how past research and policy decisions, including funding cuts and program discontinuations, have led to critical gaps in current NASA capabilities. These gaps pose a strategic risk to US leadership in human space exploration that must be addressed urgently to sustain international competitiveness. It concludes with recommendations for program investments crucial for the deployment of mature bioregenerative technologies in the coming decade.